Is overgrazing a pervasive problem across Mongolia? An examination of livestock forage demand and forage availability from 2000 to 2014 - Gao, W., author; Angerer, J. P., author; Fernandez-Gimenez, M. E., author; Reid, R. S., author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
Pastoral livestock production is considered a pillar of the Mongolian economy. Since the early 1990's, Mongolia has transitioned to a market economy, and livestock numbers have trended upward. Recent remote sensing studies have indicated widespread overgrazing; however, to date, no studies have examined grazing pressure on a national scale to assess the pervasiveness of overgrazing. We conducted a spatial and temporal analysis of grazing pressure by analyzing the relationship between livestock forage availability and forage demand across soums during 2000 to 2014. To estimate livestock forage demand (kg/ha/yr), we converted soum livestock densities to sheep forage units and calculated forage intake on an area basis. Forage availability was estimated using a regression relationship between herbaceous biomass and 250-m resolution MODIS NDVI (r2 = 0.70). The regression was applied to yearly maximum NDVI images to create surfaces of available forage (kg/ha/yr). Percent use (PU) of forage, which is the ratio of forage demand to forage available, was used as an indicator of grazing pressure. 50% use is generally recommended on rangelands for promoting forage regrowth and soil protection. Thirteen percent of the rangeland across Mongolia had PU that exceeded 50% during the entire time series, while 37% had 10 or more years with >50% use. Grazing pressure was higher in the central and western aimags, and lowest in the eastern aimags. Dzuds (winter disasters) in 1999-2002 and 2010 resulted in 35% and 22% reductions in livestock numbers nationwide. Grazing pressure exceeded 50% in over half of the country prior to and during dzuds due to the effect of summer drought on forage availability and high animal numbers. Grazing pressure was lowest after dzuds due to lower livestock numbers and forage response to higher rainfall. Our results indicate that heavy stocking (>50 PU) appears to be pervasive in about 32% of the country and consistent overgrazing (>=10 years with PU>=70) occurs on approximately 11% of the land area. During individual years, land areas having overgrazing are variable due to extreme climate events and linear increases in livestock numbers, regardless of forage availability, during periods between dzuds. The spatially explicit and temporal nature of these results will aid in disentangling effects of changing climate and management, and assessing the resilience of these rangeland systems in Mongolia.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: overgrazing; forage demand; forage availability; Mongolia